2020
DOI: 10.30650/jik.v8i2.1375
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between the Social Status and Successful of Exclusive Breastfeeding Age 6 Months to 4 Years in Rempanga Village, Loa Kulu District, Kutai Kartanegara

Abstract: The provision of breast milk is very important for infants and toddlers during the first 6 months of life. Several factors can affect exclusive breastfeeding, one of which is socioeconomic status. This research was conducted to see the relationship between the status of socio-economic and successful exclusive ASI in the Village District of Loa Kulu. The method of this research is Descriptive correlative quantitative research with a Crossectional method and using Total Sampling Design. The population of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
0
1
Order By: Relevance
“…Different findings were obtained in another study that economic status did not significantly affect exclusive breastfeeding (Winarti et al, 2020). The difference in results with this study was also found in previous studies that socioeconomic factors did not influence exclusive breastfeeding (Nazari et al, 2021).…”
Section: Discussioncontrasting
confidence: 98%
“…Different findings were obtained in another study that economic status did not significantly affect exclusive breastfeeding (Winarti et al, 2020). The difference in results with this study was also found in previous studies that socioeconomic factors did not influence exclusive breastfeeding (Nazari et al, 2021).…”
Section: Discussioncontrasting
confidence: 98%